Expanded motor and psychiatric phenotype in autosomal dominant Segawa syndrome due to GTP cyclohydrolase deficiency. Issue 1 (16th December 2005) - Van Hove, J L K; Steyaert, J; Matthijs, G; Legius, E; Theys, P; Wevers, R; Romstad, A; Møller, L B; Hedrich, K; Goriounov, D; Blau, N; Klein, C; et al.
Abstract : Background: Segawa syndrome due to GTP cyclohydrolase deficiency is an autosomal dominant disorder with variable expression, that is clinically characterised by l- dopa responsive, diurnally fluctuating dystonia and parkinsonian symptoms. Objective: To delineate the neurological and psychiatric phenotype in all affected individuals of three extended families. Methods: GTP cyclohydrolase deficiency was documented by biochemical analyses, enzymatic measurements in fibroblasts, and molecular investigations. All affected individuals were examined neurologically, and psychiatric data were systematically reviewed. Results: Eighteen affected patients from three families with proven GTP cyclohydrolase deficiency were identified. Eight patients presenting at less than 20 years of age had typical motor symptoms of dystonia with diurnal variation. Five family members had late-presenting mild dopa-responsive symptoms of rigidity, frequent falls, and tendonitis. Among mutation carriers older than 20 years of age, major depressive disorder, often recurrent, and obsessive-compulsive disorder were strikingly more frequent than observed in the general population. Patients responded well to medication increasing serotonergic neurotransmission and to l- dopa substitution. Sleep disorders including difficulty in sleep onset and maintenance, excessive sleepiness, and frequent disturbing nightmares were present in 55% of patients. Conclusion: Physicians should be aware of this expanded phenotype in affected members of families with GTP cyclohydrolase deficiency.